Negative recommendation in social media – theoretical approach and case studies - Kaniewska-Sęba, Aleksandra; Pająk-Patkowska, Beata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
The Internet, including the social media services, has considerably changed the manner in which consumers voice favourable or unfavourable recommendations about products and services. Development of social media allowed reaching a significantly greater number of persons in a quicker way. One may also notice that the range of thematic comments has been expanded – customers speak not only about the quality of the products, their prices, service levels, but also about other aspects of how marketing companies function. Finally, it is worth paying attention to the language of these opinions, which – in the case of a negative experience with a product or retailer advertising – is often aggressive. With the development and dissemination of social networking, PR and marketing communications managers must learn how to communicate and satisfy customers and those who express their discontent at different stages of the purchase funnel. This is especially important in the case of negative word of mouth (NWOM) because every negative opinion can become the nucleus of major problems within brand image and the brand crisis. The aim of the article is to show the specificity of word of mouth in social media (sWOM) as one of the forms of electronic word of mouth (eWOM) and to depict phenomenon of NWOM in social media basing on selected case studies from the Polish market.

Internet, w tym media społecznościowe, znacząco zmieniły sposób, w jaki konsumenci przekazują pozytywne bądź negatywne rekomendacje na temat produktów i usług. Rozwój mediów społecznościowych umożliwił szybsze dotarcie z takim komunikatem do znacznie większej liczby osób. Można również zaobserwować, że rozszerzył się zakres tematyczny komentarzy – klienci wypowiadają się nie tylko na temat jakości produktów, ich ceny, poziomu obsługi, ale także innych aspektów marketingowego funkcjonowania firm. W końcu, warto zwrócić uwagę na język owych opinii, który – w przypadku negatywnych doświadczeń z produktem, sprzedawcą czy reklamą – jest nierzadko agresywny. Wraz z rozwojem i upowszechnianiem się sieci społecznościowych, menedżerowie ds. PR czy komunikacji marketingowej muszą nauczyć się jak komunikować się i z usatysfakcjonowanymi klientami i tymi, którzy na różnych etapach lejka zakupowego (purchase funnel) wyrażają swoje niezadowolenie. Jest to szczególnie ważne w przypadku neagative word of mouth (NWOM) bo każda negatywna opinia może stać się zalążkiem poważnej akcji kryzysowej i problemów wizerunkowych. Celem artykułu jest ukazanie specyfiki word of mouth w mediach społecznościowych (sWOM) jako jednej z form elektronicznego WOM (eWOM) oraz zobrazowanie zjawiska negatywnej rekomendacji w social media na podstawie wybranych studiów przypadków z rynku polskiego.
Negatywna rekomendacja w mediach społecznościowych – ujęcie teoretyczne i studia przypadków
Keywords: word of mouth (WOM); rekomendacja (WOM); positive word of mouth (PWOM); pozytywna rekomendacja (PWOM); negative word of mouth (NWOM); negatywna rekomendacja (NWOM); social media; media społecznościowe